2020
DOI: 10.1016/j.cpc.2020.107288
|View full text |Cite
|
Sign up to set email alerts
|

FACt: FORTRAN toolbox for calculating fluctuations in atomic condensates

Abstract: We develop a FORTRAN code to compute fluctuations in atomic condensates (FACt) by solving the Bogoliubov-de Gennes (BdG) equations for two component Bose-Einstein condensate (TBEC) in quasi two dimensions. The BdG equations are recast as matrix equations and solved self consistently. The code is suitable for handling quantum fluctuations as well as thermal fluctuations at temperatures below the critical point of Bose-Einstein condensation. The code is versatile, and the ground state density profile and low ene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…To go beyond the linear regime of the Bogoliubov stability analysis, we simulate the full two-dimensional dynamics of the unstable composite vortices by directly evolving the timedependent GP equations (1) in time. The time evolution is performed with a split-step Crank-Nicolson method [78,79] adapted for two-component BECs [80]. To obtain a convenient initial state, we first propagate Eqs.…”
Section: Time-evolution Simulationsmentioning
confidence: 99%
“…To go beyond the linear regime of the Bogoliubov stability analysis, we simulate the full two-dimensional dynamics of the unstable composite vortices by directly evolving the timedependent GP equations (1) in time. The time evolution is performed with a split-step Crank-Nicolson method [78,79] adapted for two-component BECs [80]. To obtain a convenient initial state, we first propagate Eqs.…”
Section: Time-evolution Simulationsmentioning
confidence: 99%
“…Studying a miscible BECs based on the time-dependent Hartree-Fock-Bogoliubov theory, the author of [23] found that quantum fluctuation is proportional to the square power of the atomic interaction strengths. The numerical solving of the Bogoliubovde Gennes equations of the quantum fluctuation in BECs was reported in [24]. However, the influence of the atomic interaction on the quantum fluctuation in the immiscible phase was not mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, FACt (Fluctuations in Atomic Condensates, Roy et al, 2020) is the only publicly accessible code for the BdG problem. It considers thermal excitations of the BECs at non-zero temperatures by solving the BdG equation in two component BECs with a pseudo-spectral method.…”
Section: Introductionmentioning
confidence: 99%